Validation of a Flour-Free Model Dough System for Throughput Studies of Baker's Yeast - Panadero, Joaquin (American Society for Microbiology, 2005)
Evaluation of gene expression in baker's yeast requires the extraction and collection of pure samples of RNA. However, in bread dough this task is difficult due to the complex composition of the system. We found that a liquid model system can be used to analyze the transcriptional response of industrial strains in dough with a high sugar content. The production levels of CO(2) and glycerol by two commercial strains in liquid and flour-based doughs were correlated. We extracted total RNA from both a liquid and a flour-based dough. We used Northern blotting to analyze mRNA levels of three stress marker genes, HSP26, GPD1, and ENA1, and 10 genes in different metabolic subcategories. All 13 genes had the same transcriptional profile in both systems. Hence, the model appears to effectively mimic the environment encountered by baker's yeast in high-sugar dough. The liquid dough can be used to help understand the connections between technological traits and biological functions and to facilitate studies of gene expression under commercially important, but experimentally intractable, conditions.